Managing Hierarchically Structured DTN-Like Networks - Riku Luostarinen; Jukka Manner (Journal of Computer Networks and Communications)
Network management in Delay/Disruption Tolerant Networks (DTNs) is an active research topic and covers topics such as system architecture, roles of actors, and management protocol. The existing solutions either expect a flat management hierarchy or do not address the hierarchical structure used in management. However, in many real-world DTN use cases, particularly in emergency and military contexts, the actors using the DTN system are a part of an organizational or operational hierarchy, and the network design and topology follow the hierarchical structure. This paper introduces a DTN management scheme that is based on that hierarchy. The paper presents a node categorization that is based on the hierarchy, the characteristics of the hierarchical management, roles and responsibilities of the managed and managing nodes in the hierarchy, and the related concept of management responsibility stack. Further, the paper discusses the characteristics of the messaging and configurability of the nodes in a hierarchical network, and introduces a problem called DTN management trilemma. The paper also presents a use case where the concepts of this paper are applied to network management of a hierarchical organization in a reference scenario, and the performance of the hierarchical management methods is compared to an equivalent nonhierarchical solution.